On the Cultural Origin and Realistic Significance of the Concept of "Cultivating Virtue and Cultivating People" - Sun, Hongwei (Journal of Education and Educational Technologies, 2023)
Deeply exploring the traditional cultural origins of the concept of "cultivating virtue and cultivating people" and understanding its essence can guide educators to consciously do a good job in ideological and political education. Confucian The profound ideological origins of "benevolent love" and "introspection", "prudence and independence", Taoism's "morality" and "unspoken teaching", Mohism's "universal love", "noble righteousness", and "extreme self suffering" are all profound.